Elimination of the channel current effect on the characterization of MOSFET threshold voltage using junction capacitance measurements. (February 2017) - Tomaszewski, Daniel; Głuszko, Grzegorz; Łukasiak, Lidia; Kucharski, Krzysztof; Malesińska, Jolanta
Abstract: An alternative method for an extraction of the MOSFET threshold voltage has been proposed. It is based on an analysis of the MOSFET source-bulk junction capacitance behavior as a function of the gate-source voltage. The effect of the channel current on the threshold voltage extraction is fully eliminated. For the threshold voltage and junction capacitance model parameters non-iterative methods have been used. The proposed method has been demonstrated using a series of MOS transistors manufactured using a standard CMOS technology.